2015
DOI: 10.1016/j.foodqual.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive eater: Perceived healthiness moderates the effect of the color red on consumption

Abstract: Previous studies suggest that the color red reduces food intake because it signals danger and hence acts as a consumption-stopping cue. We demonstrate that this effect cannot be generalized to just any kind of food. Consequently, we show that the color red-despite eliciting similar associations-affects behavior more strongly with regard to unhealthy (potentially harmful) food compared to healthy food. Specifically, the color red more strongly influenced the amount of unhealthy food intake (Study 1) and the cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 27 publications
(57 reference statements)
1
34
1
1
Order By: Relevance
“…It has been estimated that flour‐based foods has huge market (c. 600 billion CNY; approximately 89 billion USD every year) in China, while noodles account for 35% of the yearly flour‐based food consumption nationwide (Liu, ). Our findings suggest a fundamental difference between the role of plateware in the subjective ratings of, and taste expectations concerning snack food consumed for hedonic values in previous studies (Bruno et al, ; Genschow et al, ; Reutner et al, ) and regularly consumed familiar and unfamiliar food as in the present study, suggesting that consumers might react to the visual cues in an adaptive way (see also Reutner et al, ). These findings have direct implications in the business of food serving in restaurants.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…It has been estimated that flour‐based foods has huge market (c. 600 billion CNY; approximately 89 billion USD every year) in China, while noodles account for 35% of the yearly flour‐based food consumption nationwide (Liu, ). Our findings suggest a fundamental difference between the role of plateware in the subjective ratings of, and taste expectations concerning snack food consumed for hedonic values in previous studies (Bruno et al, ; Genschow et al, ; Reutner et al, ) and regularly consumed familiar and unfamiliar food as in the present study, suggesting that consumers might react to the visual cues in an adaptive way (see also Reutner et al, ). These findings have direct implications in the business of food serving in restaurants.…”
Section: Discussioncontrasting
confidence: 52%
“…It should be noted that the color red (when not associated with a brand, or any other meaning) has been shown to reduce the intake of those foods that are considered unhealthy (Bruno et al, ; Genschow et al, ; Reutner et al, ); and it has been suggested that serving food from blue trays may reduce consumers' food intake compared to trays of other colors (at least in Depression‐era North America, Crumpacker, ). Note, also, how blue foods are rare in nature, so people might have worries about the safety of blue food (Suzuki et al, ) and prefer them less (Lee, Lee, Lee, & Song, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, colors may also have a symbolic value and generate particular cognitive associations (Ares & Deliza, 2010) and these associations may differ between cultures (Madden, Hewett, & Roth, 2000). For instance, the color red is a signal for danger in many societies, which may decrease consumption probability (Genschow, Reutner, & Wänke, 2012;Reutner, Genschow, & Wänke, 2015), but in China the color red is likely to have an opposite effect, because there it is associated with good luck and prosperity. Furthermore, colors may also bring their own hedonic evaluations (Madden et al, 2000;Valdez & Mehrabian, 1994;Whitfield & Wiltshire, 1990), even though color preferences highly depend on the context in which they are perceived (e.g., the size and the type of object that carries the color; Holmes & Buchanan, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Estos péptidos actúan en los receptores localizados en las fibras aferentes vagales, de manera que la información se transmite al nervio vago (31). Las ECCs están localizadas en contacto directo con el lumen y debido a esta proximidad, las bacterias comensales pueden interactuar directamente con ellas y, por tanto, modular la secreción de estos péptidos y otros metabolitos, los cuales se absorben y pasan al sistema circulatorio por transporte paracelular cuando la barrera epitelial está inflamada (32).…”
Section: El Eje Intestino-cerebrounclassified